Optical Imaging of Cancer Clinical Applications - Rosenthal, Eben.; Zinn, Kurt R. (Springer New York, 2010)
Optical detection represents the next great horizon for cancer imaging. As molecularly targeted therapeutic agents are delivered to the clinic in increasing numbers, there is a parallel opportunity to advance optical imaging techniques. Because of its limited toxicity and potential for real-time information, optical imaging represents an underdeveloped modality in clinical medicine. Optical Imaging of Cancer: Clinical Applications explores the preclinical and clinical data to support the use of these techniques in cancer imaging. Different fluorescent delivery modalities are explored: from monoclonal antibodies to viral vector delivery. Indications for use include monitoring therapuetic delivery, early detection, and operative removal techniques in all stages of clinical development. This book represents the best and most clinically relevant techniques currently available.